Indigenous peoples' relationships to large-scale mining in post/colonial contexts: Toward multidisciplinary comparative perspectives. Issue 3 (July 2018) - Horowitz, Leah S.; Keeling, Arn; Lévesque, Francis; Rodon, Thierry; Schott, Stephan; Thériault, Sophie
Highlights: Mining has particular, often disproportionate, impacts on Indigenous communities. Opportunities exist for Indigenous peoples to benefit from/shape mining projects. More research is needed on mining and Indigenous peoples in post/colonial contexts. Abstract: Because of their close relationships to the land, water, and resources therein, and their marginalized social and economic positions, Indigenous peoples living in current or former settler colonies are particularly vulnerable to mining's impacts, yet have the potential to benefit from its opportunities as well. This paper reviews the literature on large-scale mining projects' relationships to Indigenous peoples in post/colonial contexts, focusing on Australia, Canada, Finland, Greenland, New Caledonia, Norway, and Sweden, in the aim of generating insights from comparative perspectives. First, we discuss differences in legal regimes governing Indigenous peoples' rights and implications of those rights for negotiations over mining projects. Next, we examine, in turn, mining activities' various impacts − environmental, economic, social − and how they specifically affect Indigenous communities. Finally, we explore ways that Indigenous communities living in a post/colonial context have addressed large-scale mining projects' impacts by engaging with them, through both negotiation and resistance. We conclude by summarizing our findings on the relationships of Indigenous peoples to large-scale mining projects in the focus countries and identifying what gaps remain in the literature, and we provide thoughts as to how future research could address those gaps.